2022
DOI: 10.2196/38589
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Social Media Use and Online Racial Discrimination on Asian American Mental Health: Cross-sectional Survey in the United States During COVID-19

Abstract: Background During the COVID-19 pandemic, increased social media usage has led to worsened mental health outcomes for many people. Moreover, due to the sociopolitical climate during the pandemic, the prevalence of online racial discrimination has contributed to worsening psychological well-being. With increases in anti-Asian hate, Asian and Asian American social media users may experience the negative effects of online racial discrimination in addition to the reduced psychological well-being resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 141 publications
(126 reference statements)
3
2
0
Order By: Relevance
“…Due to the increased instances of racial slurs, attacks, and jokes directed toward Asians living in the United States and Canada since the start of the pandemic (Cheah et al, 2020; Ta Park et al, 2022; Wayne et al, 2021; Woo & Jun, 2022), we included questions on experiences with direct or indirect online racial discrimination. Participants reported occurrences of indirect online racial discrimination, similar to Layug et al (2022), who found adult Asian Americans reported higher indirect discrimination than Latinx and White Americans. Although Layug et al (2022) and Cheah et al (2020) found COVID-19-related discrimination predicted negative mental health outcomes, our results found no relationship between direct or indirect online racial discrimination and mental health outcomes which could be due to close knit Asian communities which may have provided a protective effect and sense of security during challenging times (Leigh et al, 2022).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Due to the increased instances of racial slurs, attacks, and jokes directed toward Asians living in the United States and Canada since the start of the pandemic (Cheah et al, 2020; Ta Park et al, 2022; Wayne et al, 2021; Woo & Jun, 2022), we included questions on experiences with direct or indirect online racial discrimination. Participants reported occurrences of indirect online racial discrimination, similar to Layug et al (2022), who found adult Asian Americans reported higher indirect discrimination than Latinx and White Americans. Although Layug et al (2022) and Cheah et al (2020) found COVID-19-related discrimination predicted negative mental health outcomes, our results found no relationship between direct or indirect online racial discrimination and mental health outcomes which could be due to close knit Asian communities which may have provided a protective effect and sense of security during challenging times (Leigh et al, 2022).…”
Section: Discussionsupporting
confidence: 52%
“…Participants reported occurrences of indirect online racial discrimination, similar to Layug et al (2022), who found adult Asian Americans reported higher indirect discrimination than Latinx and White Americans. Although Layug et al (2022) and Cheah et al (2020) found COVID-19-related discrimination predicted negative mental health outcomes, our results found no relationship between direct or indirect online racial discrimination and mental health outcomes which could be due to close knit Asian communities which may have provided a protective effect and sense of security during challenging times (Leigh et al, 2022).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations